An enquiry into antileishmanial activity and quantitative analysis of polyhydroxylated steroidal saponins from Solanum paniculatum L. leaves - Valerino-Díaz, Alexander B. [UNESP]; Zanatta, Ana C. [UNESP]; Gamiotea-Turro, Daylin [UNESP]; Candido, Ana Carolina Bolela Bovo; Magalhães, Lizandra Guidi; Vilegas, Wagner [UNESP]; Santos, Lourdes Campaner dos [UNESP] (Elsevier, 2020)
Solanum paniculatum L. is species whose fruits are widely consumed in Brazil as a tonic beverage with higher content of steroidal saponins. In this work, we developed an analytical method for the quantification of the eight saponins present in the 70 % ethanol extract from the leaves using ultra-high-performance liquid chromatography coupled to mass spectrometry (UHPLC-MS). Besides, the eight spirostanic saponins were screened for in vitro antileishmanial activity against promastigote and amastigote forms of Leishmania (L.) amazonensis. Substances 1, 2 and 3 were found to be the most active compounds, with inhibitory concentration (IC50) values of 8.51 ± 4.38, 10.75 ± 6.85 and 10.45 ± 4.21 μM, respectively, against promastigote forms and effective concentration (EC50) values of >25, 17.73 ± 0.99 and 19.57 ± 0.84 μM, respectively, against amastigote forms. The cytotoxic test with compounds 1–3 evidenced low toxicity in murine macrophage cells, with values above 50 μM at concentration lower than 25 μM. These findings show that saponins 1–3 should be evaluated in further studies for the treatment of cutaneous leishmaniasis.
Keywords: Antileishmanial activity; Leishmania amazonensis; Quantitative analysis; Solanumpaniculatum L.; Spirostanic saponins; UHPLC-ESI-MS